Chitosan-Curcumin Coating Characterization on Cobalt-Chrome Surface by 100 kHz Ultrasonic Spray Method - Katiko Imamul Muttaqin (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Curcumin possesses anticoagulant, anti-proliferative, and anti-inflammatory properties and is applicable to prevent in-stent restenosis. This research investigated curcumin coating with biodegradable chitosan polymer as a drug carrier universally made on Co-Cr L605 surface by the ultrasonic spray method. Three curcumin doses were implemented: low dose (150 μg of curcumin per sample), medium dose (300 μg of curcumin per sample), and high dose (480 μg of curcumin per sample). The metal surface morphologies before and after coating were examined by using a stylus profilometer and a scanning electron microscope (SEM). The result showed that coating films were formed fine and uniform with an average roughness level below 0.2 μm. The coating film structure characterization by Fourier-transform infrared (FTIR) spectroscopy showed that curcumin absorption spectra still occurred in the chitosan-curcumin coating, although chitosan strong absorption spectra were dominant.